The Effects of Fuel Subsidy Removal on Input Costs of Productions: Leontief Input-Output Price Model - Mukaramah Harun (International Journal of Supply Chain Management, 2018)
The study analyzes the impact of fuel subsidy removal policy on input costs of production sectors in Malaysia by applying the Input-output Price Model using Malaysia Input-output Table 2010. The elimination of subsidy on fuels such as RON95, RON97 and Diesel led to the increase in fuel prices by 32% on average. The increase in fuel prices led to an increase in production input costs for all 66 sectors, where the increase in the input costs of each sector exceeded the hike in fuel prices. There are 4 sectors whose production input costs are higher than the fuel subsidy removal policy namely fishing and aquaculture; transportation and storage; utilities; crops, animal production and hunting; and food products. Input-output price model application is an approach less commonly used in previous studies in Malaysia even though it is the most appropriate model for analyzing the impact of fuel subsidy removal on sectoral input costs. This study shows that the elimination of fuel subsidies has a major impact on the country's inflation and drastic global oil price changes can challenge the Malaysian economic sustainability.